2005 IEEE International Symposium on Circuits and Systems
DOI: 10.1109/iscas.2005.1465391
|View full text |Cite
|
Sign up to set email alerts
|

Congestion-Optimized Scheduling of Video over Wireless AD HOC Networks

Abstract: We analyze the benefits of information sharing between the application layer and the transport layer, for streaming video encoded at several different qualities, in a mobile wireless network. The application relies on statistics collected at the transport layer and on a video distortion model to select the highest quality that can be supported by the network. At the transport layer, congestion-distortion optimized scheduling is performed to select packets which maximize the received video quality. Experiments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 12 publications
0
11
0
Order By: Relevance
“…For nodes pair (7,3), in our experiments, we found that the prime route (7, 5, 3) is quite stable. We found route (7,4,3) and route (7, 3) as backup routes. We observed that there are 8 occasions when the prime route fails, 28 occasions when the backup routes fail, and on 8 occasions both routes fail simultaneously.…”
Section: Experiments Evaluationmentioning
confidence: 83%
See 3 more Smart Citations
“…For nodes pair (7,3), in our experiments, we found that the prime route (7, 5, 3) is quite stable. We found route (7,4,3) and route (7, 3) as backup routes. We observed that there are 8 occasions when the prime route fails, 28 occasions when the backup routes fail, and on 8 occasions both routes fail simultaneously.…”
Section: Experiments Evaluationmentioning
confidence: 83%
“…Here δ is the minimum rate increment, which we set to be 10 kbps. 4: else if received n NACKs and no route brokens then 5: R cur = min(R max , R cur − n · δ). 6: else if window_length > CONG_AVOID then 7: R cur = min(R max , R cur − δ).…”
Section: The Clarc Algorithmmentioning
confidence: 99%
See 2 more Smart Citations
“…TCP deploys congestion control through its congestion window mechanism, which, as stated earlier, is not very effective in wireless networks. Setton et al [17] used a mobile ad hoc network using 802.11 to implement a cross-layer scheduling for video transmission. They used a distortion model based on their earlier works.…”
Section: Congestion-optimized Video Schedulingmentioning
confidence: 99%